An Anaylsis in Order to Measure of Regional Development Agencies Performance and Their Impacts to the Regional Growth in Turkey - Ahmet Bas; Mehmet Alý Yüzer (European Regional Science Association (ERSA), 2014)
"Development" isn't only an economic notion but also it consist of so many meanings such as social, cultural manners, production and consumption ways. During the development process, development units could be growth in vary times and space. At this point what has to be told, which sector and production unit will be developed and how much money will invest in this sector? Besides, the institutional position has a crucial point during the development process and there are vary many ways in the world to accomplish the process. RDAs is one of the institutional ways of this process. RDAs are aim to enhance the development in the region by using the endogenous growth theories. In the USA, Tennesse Valley Autority was the first one that dealed with the construction of dams in the region and to ensure the production rate. In Europe, RDAs process came together after II. World War. In this paper, RDAs are studied generally and searched their institutional and legislative status around the world and Europe as well as Turkish RDAs. As the study shows that, examples from the varied countries have some similarities, but offenly the applications are changed from country to country. Such as developed countries, RDAs are specialized to bring and enhance the foreign investment and to use the national and international funds and grants, however, in less developed countries RDAs are worked to increase the usage of natural sources and to reduce the unemployment ratio. Turkish RDAs were established at 2006 and after four years later, they are able to start their facilities all around Turkey in the 26 NUTS 2 regions at 2010. The institutional frame of the Turkish RDAs are specified and constituted by local governors, NGOs and local autorities (municipalities). The head of the board of directors is local governor in the region. Besides the secretary general is responsible to the board of directors from the agency activities. Also there is an advisory committee which is named "Development Committee". In order to analyze their performances and show to change of the disparities; their facilities are studied in the paper. In this context, to analyze the RDAs' performance, 27 indicators are determined which are related to the responsibilities and duties of RDAs that are determined in the law of 5449. Moreover, these indicators are categorized and managed some exponents according to their importance. After additioning all the units, a performance score is calculated for each RDAs. Moreover, a comparison is also examined to explain the changes before and after RDSs establishment in Turkey.
Keywords: D63; P25; R11; R58; 330; Region; Regional Development; Regional Disparities; Regional Growth; Regional Development Agencies; Performance; Performance Anaylsis